Exploring the Factors Shaping Investment Decisions : Insights from Financial Literacy, Financial Behavior, and Income among Lecturers at the Faculty of Economics and Business, University of Jambi - fitriaty, fitriaty (Dinasti Publisher, 2023)
This study aims to examine the effect of financial literacy and income on investment decisions mediated by financial behavior. This study uses secondary data by distributing questionnaires to lecturers at the Faculty of Economics and Business, Jambi University. The data is processed using the smart PLS application to test the effect of each variable. The results of this study found that financial literacy and financial behavior have a significant positive effect on investment decisions, and income has a negative effect on investment decisions. Financial literacy has a significant positive effect on financial behavior, income has a non-significant positive effect on financial behavior. The financial treatment variable can mediate the relationship between financial literacy and investment decisions